Bernard Huet et la synthèse du rationalisme exalté d’Aldo Rossi - Julien Correia (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère, 2019)
The last decade has seen a renewed interest in the Italian architect Aldo Rossi, who died in 1997. The article recalls the steps and difficulty of its French reception. The aim here is to understand how Aldo Rossi’s theoretical legacy is incomplete in France and to define the contours of the missing part.This legacy is discussed on the basis of unpublished archives by Bernard Huet and a corpus of works bequeathed to the ENSA Paris-Belleville library, which make it possible to define its outlines. The synthesis of Aldo Rossi’s theoretical work by Bernard Huet will then be analysed in order to begin to identify the elements of the missing part. This will finally be defined on the basis of the presentation of two collections of texts written by Aldo Rossi which have the characteristics of being still untranslated and very little distributed in France.